Tantangan Dan Strategi PAK Anak dalam Konteks Indonesia Masa Kini - Flesia Nanda Uli Boangmanalu (STIKAS Santo Yohanes Salib Kalimantan Barat, 2023)
This article is based on the lack of growing a sense of awareness and care for children's PAK ministries in the church. So that the growth and development of children's ministry is less than optimal in the church. The challenges in implementing PAK for children and how the ministry strategy will be implemented is a problem point for church leaders. The purpose of this research is to explore the challenges that will be faced by a church leader and to find a variety of strategies that can be used in implementing children's PAK in the church. The method used is descriptive qualitative, namely analyzing, comparing and concluding various opinions from source books/journals from various experts regarding the challenges and strategies for implementing PAK for children in the church. Reviving a sense of awareness and concern for church leaders regarding the growth and development of children's PAK will help people from an early age to think for themselves in learning the process of finding God's guidance in life. And this is a very important thing to emphasize for the contemporary church in Indonesia.